Proceedings of the 3rd Gas Processing Symposium 2012
DOI: 10.1016/b978-0-444-59496-9.50021-7
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Ionic Liquids in Gas Processing

Abstract: Over the last decade ionic liquids have grown from relatively poorly understood materials to become integrated into industrial applications. These materials are, quite simply, comprised entirely of ions, and are liquid at room temperature. Given their nature, they have been described as "designer" solvents, with "tuneable" features that can be adjusted to suit the requirements of a particular process. A huge interest in using ionic liquids as an alternative medium for gas separation has become apparent because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Therefore, the use of ILs for gas capture and in particular CO 2 capture has received interest in recent years because of their unique characteristics and high solubilities. 195,196 More specifically, by modification of solvent properties at room temperature through hydrogen-bond donors, IL mixtures may have great potential for efficient CO 2 absorption. 86 Deep Eutectic Solvents and Gas Solubility Studies.…”
Section: Carbon Dioxide Capture and Gasmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the use of ILs for gas capture and in particular CO 2 capture has received interest in recent years because of their unique characteristics and high solubilities. 195,196 More specifically, by modification of solvent properties at room temperature through hydrogen-bond donors, IL mixtures may have great potential for efficient CO 2 absorption. 86 Deep Eutectic Solvents and Gas Solubility Studies.…”
Section: Carbon Dioxide Capture and Gasmentioning
confidence: 99%
“…Some recent works have shown that ILs are very promising alternative capture solvents, mostly for CO 2 and other toxic gases such as H 2 S and SO 2 as well. The physical and chemical properties of ILs at various temperatures (mostly at room temperature) can be adjusted through modification of their cationic and anionic moieties, allowing them to be tailored for various applications and process needs such as making solvents, solid-state photocells, and thermal and hydraulic fluid lubricants. Bates et al attempted to modify the cation of imidazolium-based ILs through the attachment of a primary amine moiety, which subsequently has high affinity and can capture CO 2 through carbamate formation. Therefore, the use of ILs for gas capture and in particular CO 2 capture has received interest in recent years because of their unique characteristics and high solubilities. , More specifically, by modification of solvent properties at room temperature through hydrogen-bond donors, IL mixtures may have great potential for efficient CO 2 absorption…”
Section: Carbon Dioxide Capture and Gas Separationmentioning
confidence: 99%